Fragmented Selves, Fragmented Lives and Fragmented Movies: A Reading of Fight Club - Ezgi Sertalp (Momentdergi, 2016)
The present study aims to address postmodernism, which is called as the post-industrial society or consumer society, as the media or spectacle society, or as multi-national capitalism by Fredric Jameson, within its social, cultural and economic context, and examines how it is transformed into the consumer culture and consumer society and how this transformation affects individuals’ own selves, identities and daily practices. Considering Jameson’s suggestion that the main work of art representing postmodern society is film, the movie Fight Club will be analyzed in light of the concepts ‘fragmented self’ and ‘fragmented life’. The movie Fight Club, a significant product of the 1990s Hollywood cinema the products of which are also called as postmodern movies as a result of all the developments and transformations within the society, is believed to be a convenient ground for a discussion of the relation between postmodernism and fragmentation.